PEMBIASAAN KEGIATAN KEAGAMAAN DALAM MEMBENTUK KARAKTER RELIGIUS SISWA SEKOLAH DASAR DI ERA DIGITAL - Ainun Nadlif; Supriyadi, Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Forming students' religious character in the digital era is a very important and relevant issue in the world of elementary education, considering the rampant phenomenon of bullying cases, students abandoning the obligation to pray, lack of manners and morals. To overcome these problems, Kedungrawan 2 Sidoarjo Elementary School implemented the habituation of religious activities in an effort to form religious character. This study aims to describe the habituation of religious activities in forming religious character. This research uses a qualitative approach with a case study type of research.. The source of research data in this study was obtained by observation, documentation, and interview techniques with the principal, class teachers, and students. The research instrument used the researcher himself, interview guidelines, and other supporting devices including recording devices, cameras, and notebooks. The data analysis used is the Miles, Huberman and Saldana interactive model analysis which includes three elements of activity, namely data condensation, data presentation, and drawing conclusions. The validity of the data uses triangulation of sources and techniques. The results of this study indicate that the habituation of religious activities in forming students' religious character in the digital era is carried out by getting used to reading prayers, reading Juz Amma, and getting used to praying Dhuha in congregation. Keywords: Habituation, Religious activity,Formation, Religious Character, Digital Era